Non-destructive Investigation of Paintings on Canvas by Continuous Wave Terahertz Imaging and Flash Thermography; Journal of Nondestructive Evaluation; Vol. 36, iss. 2 - Zhang H.; Sfarra S. Stefano; Saluja K. Karan; Peeters J. Jeroen; Fleuret J. R. Julien; Duan Y. Yuxia; Fernandes H. C. Henrique Coelho; Avdelidis N. P.; Ibarra-Castanedo C. Clemente; Maldague X. Xavier (2017, 2017)
Title screen